Case report: Robust response of metastatic clear cell sarcoma treated with cabozantinib and immunotherapy - Sidlik Muskatel, Rakefet; Pillar, Nir; Godefroy, Jeremy; Lotem, Michal; Goldstein, Gal (Frontiers in Pediatrics, 2022)
Clear Cell Sarcoma (CCS), also referred to as malignant melanoma of soft parts, is a rare and aggressive malignant tumor. It comprises 1% of all soft tissue sarcomas and is known to be radio- and chemotherapy resistant. CCS shares morphological and immunohistochemical features with malignant melanoma, including melanin biosynthesis and melanocytic markers. However, it is distinct for the presence of EWSR1-ATF1 translocation which activates MITF transcription factor. We report here of an aggressive case of CCS in a 9-year-old patient, which demonstrates the critical role of molecular analysis in the diagnosis and treatment of uncommon cancer variants in the era of personalized medicine. The EWSR1-ATF1 translocation induces pathological c-Met activation, and so, following unsuccessful CTLA4 and PD-1 blockade immunotherapy, the child received cabozantinib, a small molecule tyrosine kinase inhibitor, with the intent to block c-Met oncogenic effect. In parallel, active immunization, using hapten di-nitrophenyl modified autologous tumor cells was administered with monotherapy PD-1 inhibitor nivolumab. Under this ‘triplet’ therapy, the patient attained an initial partial response and was progression-free for two years, in good performance status and resumed schooling. Based on our observation, cabozantinib can be used as an effective and potentially life-prolonging treatment in CCS. We suggest that priming the child’s immune system using her autologous tumor and combating T cell exhaustion with PD-1 blockade may have synergized with the targeted therapy. Combining targeted and immunotherapy is a rapidly growing practice in solid tumors and provides a glimpse of hope in situations that previously lacked any treatment option.